You are on page 1of 7

# Lecture 3: Trig identities. Complex loci.

Aim Lecture See how complex numbers can demystify some trig identities. Plot some complex loci. Basic Formulae Facts 1.ei = ei
1 2. sin = 2i (ei ei ) 3. cos = 1 (ei + ei ) 2

## 2. (3. is similar) ei ei = (cos + i sin ) (cos i sin ) = 2i sin

1 sin = 2i (ei ei ).

Trigonometric polynomials
1

## Defn A trigonometric polynomial is a fn of the form T () = a0 +

N n=1(an cos(n) + bn sin(n))

for some an, bn R. Rem: 1. If N = , we call it a trigonometric series. 2. T () is periodic & 2 is a period. You can convert any poly in cos & sin into a trig poly. e.g. 1 Write sin4 as a trig poly. A Use fact 2 and Binomial Thm (a + b)n =
n nk k n b k=0 k a n! where n = (nk)!k! k e.g. 4 = , 4 = 0 1 4 1 sin4 = 2i (ei ei )
2

1 = 8 cos 4

## N.B. sin4 is an even Uses sin4 d

Rem Fourier theory (taught in 2nd yr) shows that any nice fn of period 2 can be expanded using e.g. 2 Write sin 3, cos 3 as a poly of sin , cos . A De Moivre = cos 3 + i sin 3 = (cos + i sin )3 = cos3 +3(cos2 )i sin +3(cos )i2 sin2 +i3 sin3 = cos3 + 3i cos2 sin 3 cos sin2 i sin3 Equate real & imag parts
3

cos 3 = cos3 3 cos sin2 sin 3 = The answer is not cos 3 = cos3 3 cos (1 cos2 ) = 4 cos3 3 cos . Harder example e.g. 3 Find := cos + cos 3 + . . . + cos(2n + 1). A = Re (ei + ei3 + . . . + ei(2n+1) ) But the sum of the GP with common ratio e2i := ei + ei3 + . . . + ei(2n+1)
ei(2n+3) ei = e2i 1 Now ei2 1 = ei (ei ei )

4

## Dividing these two gives

i(n+1) sin(n+1) =e sin

= Re = cos(n + 1)

sin(n+1) sin

Complex loci

If we represent z = a + bi, w = c + di as the vectors (a, b), (c, d) then z w = (a c) + i(b d) is represented by the vector v from w to z in Argand diagram. Note: For vector v as in picture 1. | v | = |z w| 2. Dirn of v is given by Arg z w.
5

## see MATLAB geom2.m le Triangle Inequality For u, v, w C |u w| |u v| + |v w|

e.g. 4 Sketch S := {z C |Im z = |z i|} i.e. locus of points equidistant from the real axis and i. A Consider z = x + iy S, x, y, R. Im z = y. |z i| = |x + (y 1)i| = Equating and squaring gives y 2 = x2 + y 2 2y + 1. Thus y = 1 (x2 + 1). 2 x2 + (y 1)2

e.g. 5 Sketch 0 Arg z 3 2 A Arg z 3 = 3 Arg z + 2n for some n Z. 0 3Arg z = 2 OR 2 3Arg z 3 = 2 OR 2 3Arg z 5 = 2